(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Community service as a step to socialize the Creative Economy through this Technopreneur Training involving Muhammadiyah teachers from elementary to middle and high levels in the Muhammaduyah Regional Leadership, Tasikmalaya City is intended that teachers can operate the businesses in their free time wiyh online businesses by utilizing HP or Laptop/PC technology devices. Making products for training participants can be as producers in the form of culinary, merchandise, etc., or as resellers or as affiliates of goods or services that are created in such a way as top products. The implementation of this training event was held on November 20, 2021 in the Auditorium of the University of Muhammadiyah Tasikmalaya. Community Service Activities had done well, this can be measured from the level of participation during the training who had high enthusiasm and responsibility. This activity is expected to motivate Muhammadiyah teachers in order to improve the community’s economy in their respective places or regions.